Key performance indicators: contemporary challenges to industrial small and medium enterprises - Rūta Banelienė (Estonian Academy Publishers, 2021)
The paper investigates key challenges to the successful management of industrial small and medium enterprises (SMEs) under conditions of globalization and provides a model for successful evaluation and monitoring of SME activities. The proposed model is universal and could be applied by industrial SMEs with modest effort for developing databases such as product/material, equipment and production, as well as for measuring and monitoring the suggested key performance indicators (KPIs) in nine value chains: 1) inbound logistics 2) operations 3) outbound logistics 4) marketing and sales 5) service 6) human resources management 7) technology development 8) procurement 9) sustainability. The first three value chains serve as a cornerstone of all KPIs for the house of an industrial SME, while marketing and sales, and service value chains are intended to measure a companys success via sales. Procurement KPIs should focus on measuring and monitoring the stock level as continuous flow, which would secure smoothness in all the operations of the company. However, special attention should be paid to human resources management, innovations and sustainability by setting and monitoring KPIs within the whole timeframe the present, past and future.